The microbiome and precision oncology: an emerging paradigm in anticancer therapy. (2nd November 2022) - Bhat, Shabir Ahmad; Kaur, Rajandeep; Chauhan, Anshika; Pal, Arnab
Abstract: Understanding the host-microbiome interactions has emerged as an essential factor in improving human health and disease. Recent advances in understanding the intimate relationship of microbes with the host have uncovered various previously unknown underlying causes of disease development, progression, and treatment failure. The dynamic behaviour of the microbiome confers the heterogeneity in treatment response by modulating the immune response and inflammation in various diseases, including cancer. The growing insights into the microbial modulation of cancer through immunoregulation, xenometabolism, and increase in toxicity open a new era of personalised medicine. In the current review, we discuss the essential roles played by the microbiome in modulating the efficacy and toxicity of anticancer therapies (immunotherapy, chemotherapy, and radiotherapy). We also outline the current state of personalised medicine in the context of cancer and microbiome modulation. The knowledge about the role of cancer-microbiome communication will lead to designing other precise microbial modulation strategies for cancer treatment through enhanced efficacy and decreased toxicity.